A new interpretation of the sedimentary environment before and during eruption of the Emeishan LIP, Southwest China - Wang, Yu; Luo, Zhaohua; Wu, Peng; Chen, Lilu; Hao, Jinhua (International geology review, 2014)
The environment where the Permian Emeishan large igneous province (LIP) of Southwest China erupted remains controversial, especially regarding whether it was terrestrial, involving a 1 km scale domal uplift, or submarine. Slightly younger Daqiao conglomerate and Binchuan pillow lavas suggest that the Emeishan LIP erupted in a submarine environment. We show that at Binchuan, sandstone and rhyolite lie beneath the pillow lavas. In the Daqiao cross-section, there is an eastwards-verging syncline that reverses the succession of basalt and conglomerate. The conglomerate is not a basal conglomerate, and it does not contain any magmatic hydrovolcanic deposits. The basalt underlying the conglomerate is not the first of the LIP eruptions; that first eruption is found ~420 m below, on top of the Permian Maokou limestone. All together, these observations show that the deposits, including the conglomerate and pillow lava, do not represent the environment at the very start of the LIP volcanic eruptions, but represent conditions that existed before and possibly during the Emeishan LIP eruptions. Based on field investigations, the petrology of the rocks, and structural features, we conclude that submarine sedimentation and subaerial basalt eruptions coexisted in time and space in the region during or prior to the Emeishan LIP basalt eruptions.